A hydrogen bond cross-linked luminescent supramolecular network polymer and its application for the detection of alkyl iodides with differentiation capabilities from aromatic iodides. (12th October 2021) - Behere, Ravi Prakash; Rajlaxmi,; Gupta, Neelam; Roy, Susmita; Gautam, Ram Nayan; Bharty, Manoj Kumar; Chakroborty, Chanchal; Kuila, Biplab Kumar
Abstract : A luminescent supramolecular polymer consisting of poly(4-vinyl pyridine) and perylene diimide was prepared through a H-bond cross-linking strategy and used for alkyl iodide sensing. Abstract : Here, we have demonstrated a luminescent network polymer through a H-bond cross-linking strategy by connecting poly(4-vinyl pyridine) chains with perylene diimide (PDI) cross-linker. The formation of a network structure through hydrogen bonding is successfully proved from the combined study of FTIR, NMR, XRD, and viscosity. The XRD study indicates improved crystallinity with an increased number of sharp reflection peaks, whereas the AFM study reveals self assembly into fibrils and sphere-like nanostructures. These network polymers have been used for the first time for fluorometric detection of a range of commonly employed alkylating agents at low concentrations. Interestingly, the network polymer can also differentiate between alkyl iodides and aromatic iodides.